A Cross-sectional Study of KLKB1 and PRCP Polymorphisms in Patient Samples with Cardiovascular Disease - Gittleman, Haley R.; Merkulova, Alona; Alhalabi, Omar; Stavrou, Evi X.; Veigl, Martina L.; Barnholtz-Sloan, Jill S.; Schmaier, Alvin H. (Frontiers in Medicine, 2016)
Plasma kallikrein formed from prekallikrein (PK) produces bradykinin from kininogens and activates factor XII. Plasma PK is activated by factors XIIa, XIIa or prolylcarboxypeptidase (PRCP). A cross-sectional investigation determined if there is an association of PRCP and KLKB1 polymorphisms with cardiovascular disease. DNA was obtained from 2243 individuals from the PEACE trial. Two PRCP SNPs, rs7104980 and rs2298668 and 2 KLKB1 SNPs, rs3733402 and rs3087505, were genotyped. Logistic regression models were performed for history of diabetes, MI, stroke, angina, angiographic coronary disease, CABG, intermittent claudication, PTCA, and TIA. The PRCP SNP rs7104980 increased the odds of having a history of PTCA by 21% [OR = 1.211; 95% CI = (1.008, 1.454)]; P= 0.041, but was non significant after Bonferroni correction. Alternatively, having the G allele for rs3733402 (KLKB1 gene) decreased the odds of having a history of angiographic coronary disease by 24% [OR = 0.759; 95% CI = (0.622, 0.927)]; P = 0.007 that was statistically significant (p<0.01) after Bonferroni correction for multiple hypothesis testing. When the best-fit model based on the Akaike information criterion (AIC) controlled for age, weight, gender, hypertension, and history of angina. the G allele of KLKB1 rs3733402 that is associated with less plasma kallikrein activity correlated with reduced history of cardiovascular disease